2018
DOI: 10.1136/bmjopen-2017-018755
|View full text |Cite
|
Sign up to set email alerts
|

Impact of parental weight status on children’s body mass index in early life: evidence from a Chinese cohort

Abstract: ObjectivesTo understand whether parents’ weight status before conception predicts body mass index (BMI) of their offspring in early life and the differences between the mother–child and father–child associations.DesignA birth cohort study.SettingConducted at the Community Health Service Centre in Shenyang, Wuhan and Guangzhou.ParticipantsA total of 2220 live birth newborns were recruited randomly after consent of their parents, and 1178 were followed up until 2 years old.MethodsParental demographics, maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
3
9
0
1
Order By: Relevance
“…We were able to observe that overweight in mothers was associated with PROW (p 0.00) and with overweight (p 0.00) in a statistically significant way. Other studies report similar findings, where overweight and obesity in parents lead to the development of these conditions in minors [9][10][11], and relate the appearance of chronic and metabolic diseases in adult children of obese parents [7,22,23]. With respect to the socioeconomic determinants, we were able to observe that severe food insecurity was significantly associated (p 0.02) with an increase in BMI in mothers.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We were able to observe that overweight in mothers was associated with PROW (p 0.00) and with overweight (p 0.00) in a statistically significant way. Other studies report similar findings, where overweight and obesity in parents lead to the development of these conditions in minors [9][10][11], and relate the appearance of chronic and metabolic diseases in adult children of obese parents [7,22,23]. With respect to the socioeconomic determinants, we were able to observe that severe food insecurity was significantly associated (p 0.02) with an increase in BMI in mothers.…”
Section: Discussionsupporting
confidence: 85%
“…The associations between nutritional status in early childhood and future risk of chronic diseases have been well studied; these associations may be linked to genetic or environmental factors during pregnancy [7][8][9]. The evidence has also shown that the mothers' nutritional status [10][11][12], has an impact on the offspring's nutritional status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the particular cases of Southern European countries that present high prevalence of OW (5,6,29,30) , it is especially relevant to study the determinants and tracking of OB since earlier ages (31) . Although studies have been conducted in other non-European countries (32,33) , the OB prevalence found in adults in such studies was lower than that found in Portugal and therefore the parental influence can be different.…”
mentioning
confidence: 73%
“…In the Fels Longitudinal Study cohort, a western cohort from the United States of America, this relationship was stated to be stronger for daughters than for sons, as well as to be observed earlier in the life of daughters than sons [47]. However, in an Asian cohort of Chinese respondents, this association was observed only after birth and it was mild [48]. Therefore, it may be concluded that such associations may be dependent on the country, or even on the ethnicity.…”
Section: Determinants Of Program Adherencementioning
confidence: 99%